Field evaluation of the potential effects of polymer and silica-based nanopesticides on strawberries and agricultural soils - Galhardi, Juliana A. [UNESP]; Wang, Peiying; Bueno, Vinicius; Ghoshal, Subhasis; Gravel, Valerie; Wilkinson, Kevin J.; Bayen, Stephane (Royal Soc Chemistry, 2022)
Polymeric and SiO2 nanoparticles can be used as nanocarriers to improve the efficacy of pesticide delivery in agriculture. However, the environmental fate and potential risks of this type of nanopesticides in agroecosystems remain poorly understood. In this study, two separate active ingredients, azoxystrobin (AZOX) and bifenthrin (BFT), loaded into two different types of nanocarriers (Allosperse (R) polymeric nanoparticles and SiO2 nanoparticles), were applied to strawberry plants under realistic field conditions over two growing seasons. The pesticide concentration profiles in soil and plant tissues, plant growth and soil microorganisms were compared among treatments. Although the encapsulation appeared to reduce retention of the active ingredients (AI) to the soils, few of the sensitive indicators of ecosystem health showed any differences when compared to controls. Bioaccumulation of the AI by the strawberry plants and fruit was similar for classical and nano-applications of the AI. No significant differences were observed among the conventional, nanopesticide or control treatments in terms of fruit mass, number of flowers and leaves, or biomass. None of the pesticide formulations appeared to systematically affect soil enzyme activity. Finally, the soil microbial composition (Shannon indices, Principal Coordinate Analysis plots) and function (soil enzyme activity) only showed some transient, initial effects due to the pesticides, but did not distinguish among formulations.